Strategic Approach for Optimizing of Zakah Institution Performance: Customer Relationship Management - Estu Widarwati; Nur Choirul Afif; Muhamad Zazim (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2016)
Zakah is part of the Indonesian economy, which requires the development and structuring. The funds of zakah must be well managed by organizational zakah system which should be improved its performance. Therefore, there is a need of new approach concerning the zakah management based on muzakki’s behavior as an important resource in zakah institution. This paper explores the role of Customer Relationship Management (CRM) in zakah institution linked the important of muzakki’s contribution who use services of its. Then it aims to expand the understanding about how CRM as one of strategic approach for organization such zakah institution to improve its performance which employes three main aspect of CRM, which are form of personnel (behavior of personnel), business process, and using technology. Furthermore, this paper tries to depict how CRM is able to raise the zakah funds collection from Moslem society especially Middle Class Moslem in Indonesia by customer (muzakki) satisfaction and cost reduction of zakah institution.DOI: 10.15408/aiq.v9i1.4010